(3fRgI GdfGXQjf hJMaI GdbGUOjf aj TQM efGRd GdSGFQjfs - (3CHh YHO Gddg eMeO Hf efUhQ Hf eMeO Hf EHQGgje Hf eMeO Hf YHO Gdedcs; (3YHO Gddg Hf eMeO Hf Ydj GdCfUGQj GdgQhj, CHh ESeGYjd,J (B481 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi aJM dCgd GdHQjI ef GdSGdcjfp CHhGH GdeYGedGJ s
(3BNQgG (B:s
(3heQTOfG Edi WQjb GdSYGOI hYdi LejY GdCfHjGA hGdeQSdjf hBejf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B122 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B133s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B_ (3GdeZQH (B(86) s
Keywords: (3GdJhMjO hGdedd hGdfMds